2019
DOI: 10.1101/818419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of Nrxn1α within excitatory forebrain circuits drives value-based dysfunction

Abstract: Goal-directed behaviors, complex action sequences that maximize reward, are essential for normal function and are significantly impaired across neuropsychiatric disorders. Despite extensive associations between genetic mutations and these brain disorders, the mechanisms by which candidate genes contribute to goal-directed dysfunction remains unclear, owing to challenges in (1) describing aspects of reward processing that drive goal-directed dysfunction, (2) localizing these deficits to specific brain circuits … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 94 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…Our findings show that loss of α2δ-1-signalling disrupts this adaptive step. We used the PR test to measure effort exertion, because it avoids the confound of having to select between different options, such as choosing between two actions with different probability of reward or two different locations with different rewards 20,38,40,68,93,94 . In fact, PR test is a standard test to measure effort exertion both in rodents and humans 37,[84][85][86] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings show that loss of α2δ-1-signalling disrupts this adaptive step. We used the PR test to measure effort exertion, because it avoids the confound of having to select between different options, such as choosing between two actions with different probability of reward or two different locations with different rewards 20,38,40,68,93,94 . In fact, PR test is a standard test to measure effort exertion both in rodents and humans 37,[84][85][86] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, learning the action-outcome relationship requires the dorsomedial striatum (DMS) 29, 32 , which is a hub for many cortical inputs 33, 34 . Particularly, the inputs coming from the prefrontal cortex (PFC) to the DMS play critical roles in instrumental training, such as learning the action- outcome contingency 31, 35, 36 , evaluation of an outcome’s value 30, 37, 38 , and deciding between different actions or outcomes 39, 40 . However, the cellular and molecular mechanisms underlying the remodeling of these cortico-striatal circuits during learning and how their functions control goal-directed actions are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is an interesting future question as to whether this thalamic disinhibition can explain both simple motor phenotypes (e.g. hyperactivity, aggression) (Etherton et al, 2009;Grayton et al, 2013) and more complex reward processing deficits observed in mice with Nrxn1α mutations (Alabi et al, 2019). It is worth noting a recent study of the Tsc1 deletion ASD mouse model, which exhibited increased corticostriatal connectivity selectively onto dSPNs, with synaptic strength unperturbed at thalamostriatal synapses (Benthall et al, 2018).…”
Section: Changes To Striatal Circuit Output and Its Implicationsmentioning
confidence: 99%